Perlawanan Keratuan Islam Darah Putih Terhadap Kolonialisme Belanda di Lampung Tahun 1850-1856 M - Binti Fadilah Arfi (JUSPI (Jurnal Sejarah Peradaban Islam), 2017)
This study is a local study that discusses the resistance movement of Keratuan Islam Darah Putih against Dutch colonialism in South Lampung in 1850-1856 M. Keratuan Islam Darah Putih is one of the rulers in Lampung who have blood relation with the sultanate of Banten. Discussion of the resistance movement is a continuation of the existing research by focusing the year 1850-1856 as the process and the mounting of the Islamic community resistance movement in Lampung and the end of the existing Islamic government in Lampung, namely Keratuan Islam Darah Putih. In addition, the unity of the Keratuan Islam Darah Putih in 1850-1856 was a large-scale resistance involving some communities of Banten and Lampung. The discussion to be studied in this study includes several important points. First, the circumstances of Lampung before the Resistance of the Keratuan Islam Darah Putih, the two processes of the resistance movement, from preparation to war, and thirdly, the impact of the resistance movement. The method used in this research is historical research methods include heuristics, criticism, interpretation, and historiography.